2012
DOI: 10.1080/21507716.2012.662573
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Decision Making and Genetic Predisposition to Sudden Cardiac Death

Abstract: Background With current genetic technology, it is possible to detect mutations associated with long QT syndrome (LQTS), a hereditary cardiac arrhythmia syndrome. As a result, prospective parents diagnosed with LQTS will have to decide whether or not to prevent its transmission to future generations, either by not procreating or through the use of assisted reproductive technologies or prenatal testing. This paper explores how a hereditary predisposition to sudden cardiac death can influence reproductive decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Studies of views toward prenatal testing among people with genetic conditions and disabilities have found them to vary both between and within disability groups (e.g. Ahmed et al, 2015;Barlevy, Wasserman, Stolerman, Erskine, & Dolan, 2012;Chen & Schiffman, 2000;Middleton, Hewison, & Mueller, 1998). These attitudes are influenced by personal attitudes about and experiences with disability, as well as disability identity and involvement with disability culture and community 1 (Boardman & Hale, 2018;Boardman, Young, & Griffiths, 2018;Gollust, Thompson, Gooding, & Biesecker, 2003;Roadhouse et al, 2018;Stern et al, 2002).…”
mentioning
confidence: 99%
“…Studies of views toward prenatal testing among people with genetic conditions and disabilities have found them to vary both between and within disability groups (e.g. Ahmed et al, 2015;Barlevy, Wasserman, Stolerman, Erskine, & Dolan, 2012;Chen & Schiffman, 2000;Middleton, Hewison, & Mueller, 1998). These attitudes are influenced by personal attitudes about and experiences with disability, as well as disability identity and involvement with disability culture and community 1 (Boardman & Hale, 2018;Boardman, Young, & Griffiths, 2018;Gollust, Thompson, Gooding, & Biesecker, 2003;Roadhouse et al, 2018;Stern et al, 2002).…”
mentioning
confidence: 99%
“… Published reports that have analyzed different themes from this research team include: Barlevy et al , who addressed reproductive decision-making in the context of genetic predispositions to sudden cardiac death [18]; Cohen et al , who discussed special considerations for genetic testing with adolescents [19]; Erskine et al , who described the advantages of an interdisciplinary approach to personalized medicine [20]; Linder et al , who identified major concerns associated with an implantable cardioverter-defibrillator (ICD) [21]; and Erskine et al , who analyzed motivations to pursue genetic testing in individuals with a personal or family history of cardiac events or sudden cardiac death [22]. The entire data set is available from the corresponding author.…”
mentioning
confidence: 99%
“… Authors’ Note Four previously published reports have used brief examples of preliminary data from the same database. Barlevy, Wasserman, Stolerman, Erskine, and Dolan (2013) addressed reproductive decision making in the context of genetic predisposition to sudden cardiac death. Cohen, Stolerman, Walsh, Wasserman, and Dolan (2013) discussed special considerations for genetic testing with adolescents.…”
mentioning
confidence: 99%